2010
DOI: 10.1016/s1470-2045(09)70362-6
|View full text |Cite
|
Sign up to set email alerts
|

Collateral damage: toxic effects of targeted antiangiogenic therapies in ovarian cancer

Abstract: First-line chemotherapy fails in more than 20% of patients with epithelial ovarian cancer and about 40–50% of women who respond to initial treatment relapse within 2 years. In the recurrent setting, second-line chemotherapeutic agents have a 15–20% response rate with no cures. Fortunately, clinical investigations that have assessed the efficacy of new, biologically targeted therapies have reinvigorated therapeutic options for patients living with ovarian and other malignancies. In view of the fact that ovarian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
57
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(58 citation statements)
references
References 93 publications
(132 reference statements)
0
57
0
1
Order By: Relevance
“…The importance of neoangiogenesis in ovarian cancer has been proven in human patients, where several phase II clinical trials with antiangiogenic compounds used as single agents to pretreat women resulted in a 16-21% response rate (26). These trials were instrumental for the randomized phase III studies [gynecologic oncology group (GOG) 218 and that compared the added use of bevacizumab with the standard i.v.…”
Section: Discussionmentioning
confidence: 99%
“…The importance of neoangiogenesis in ovarian cancer has been proven in human patients, where several phase II clinical trials with antiangiogenic compounds used as single agents to pretreat women resulted in a 16-21% response rate (26). These trials were instrumental for the randomized phase III studies [gynecologic oncology group (GOG) 218 and that compared the added use of bevacizumab with the standard i.v.…”
Section: Discussionmentioning
confidence: 99%
“…In view of the functions of anti-angiogenic agents on normal physiological processes (14), it has become more evident that female fertility may be temporarily or permanently affected. The half-life of bevacizumab is estimated to be ~20 days (range, 10-50 days).…”
Section: Effect Of Bevacizumab On Ovarian Functionmentioning
confidence: 99%
“…However, introduction of targeted agents with anti-angiogenic properties may negatively affect ovarian function in patients of reproductive age. The effects of bevacizumab therapy on reproductive function have not been clearly determined; however, it is crucial to elucidate this toxicity by investigating the effects of anti-angiogenic agents at the molecular level and what physiologically important roles these processes play in healthy tissues (14). The aim of the present review was to discuss the unintended effects of an anti-angiogenic agent, bevacizumab, on ovarian function, and suggest strategies for the treatment of women of reproductive age.…”
Section: Introductionmentioning
confidence: 99%
“…As VEGF mediates physiologically important processes in healthy tissues, VEGF-targeting agents are associated with unique and potentially problematic side effects (Stone et al, 2010). Hypertension is the most common side effect of VEGF-targeting agents.…”
Section: Toxic Effects Of Vegf-targeting Agentsmentioning
confidence: 99%
“…However, it is speculated that the suppression of nitric oxide production by VEGF antagonism leads to vasoconstriction and decreased sodium ion renal excretion, which results in elevated blood pressure (Izzedine et al, 2009). A recent review of the adverse effects of anti-angiogenic therapies suggested that the incidence of grade 3/4 hypertension in patients that had been treated with bevacizumab, aflibercept, or TKI was 8-26%, 9-32%, and 5-48%, respectively (Stone et al, 2010). Proteinuria is another common side effect observed in patients treated with bevacizumab or aflibercept.…”
Section: Toxic Effects Of Vegf-targeting Agentsmentioning
confidence: 99%